Diffuse Intrinsic Pontine Gliomas Exhibit Cell Biological and Molecular Signatures of Fetal Hindbrain-Derived Neural Progenitor Cells - Sun, Yu (Neurosci Bull, 2019)
Diffuse intrinsic pontine glioma (DIPG) is the main cause of brain tumor-related death among children. Until now, there is still a lack of effective therapy with prolonged overall survival for this disease. A typical strategy for preclinical cancer research is to find out the molecular differences between tumor tissue and para-tumor normal tissue, in order to identify potential therapeutic targets. Unfortunately, it is impossible to obtain normal tissue for DIPG because of the vital functions of the pons. Here we report the human fetal hindbrain-derived neural progenitor cells (pontine progenitor cells, PPCs) as normal control cells for DIPG. The PPCs not only harbored similar cell biological and molecular signatures as DIPG glioma stem cells, but also had the potential to be immortalized by the DIPG-specific mutation H3K27M in vitro. These findings provide researchers with a candidate normal control and a potential medicine carrier for preclinical research on DIPG.